Pin-retain for restoration of widely tooth damaged - Ira Widjiastuti (Dental Journal (Majalah Kedokteran Gigi), 2007)
Widely damaged tooth involves enamel as well as dentin could be due to caries or other causes, resulted the preparation of retention could not be fulfilled so that additional pin is used as retention. Pin is made of titanium and used as retention for restoration with the aim to unite restorative material in tooth cavity by filling the hole that is prepared in the dentin. The number of pins that are needed is according to the width of the lost tooth tissue. Restoration with pin functions as retention has conservative advantage to the tooth structure, increases retention, resistance, period of treatment is short, and the cost is cheaper.